Creatine supplementation: facts and myths - Kawecka, Weronika; Zalewski, Paweł; Wróblewski, Wiktor; Biłogras, Jan; Borowska, Martyna; Wróblewski, Jakub (Quality in Sport, 2024)
Introduction: Creatine (N-methylguanidinoacetic acid) is a peptide built of three amino acids: glycine, arginine and methionine. Its function is to store energy. It is common practice to intake creatine as a dietary supplement. Because of that, we decided to try to answer the question if there are scientifically documented advantages of creatine supplementation. Review method: We analyzed the newest research conducted from 2017 to 2024. The studies were searched in online databases like PubMed and Google Scholar. We focused on the impact of creatine supplementation on the ageing population, professional athletes, the course of some diseases, cognitive functions and body composition Results: Creatine supplementation is beneficial in professional sports. There are some signals that creatine may worsen lung conditions in sportsmen. In the ageing population, creatine supplementation boosts the results of resistance training on ageing muscle performance. There are suggestions that in this population bone geometry changes due to a combination of training and creatine supplementation may be protective against hip fracture. Creatine can also enhance cognitive functions as well as lead to positive changes in body composition. Supplementation of creatine seems to reduce symptoms of long COVID-19. It may be also beneficial among children with dermatomyositis and patients with ischemic heart disease. Conclusions: Creatine supplementation may be beneficial in some populations. It can also enhance cognitive functions as well as lead to changes in body composition. Some effects of creatine supplementation are still controversial and further investigation is needed to determine its usefulness. Keywords: creatine, body composition, long COVID-19, ageing population, professional sport, cognitive functions, dermatomyositis, ischemic heart disease